2020
DOI: 10.1002/jmv.26625
|View full text |Cite
|
Sign up to set email alerts
|

The use of renin–angiotensin–aldosterone system (RAAS) inhibitors is associated with a lower risk of mortality in hypertensive COVID‐19 patients: A systematic review and meta‐analysis

Abstract: Renin–angiotensin–aldosterone system (RAAS) inhibitors, including angiotensin‐converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are one of the most prescribed antihypertensive medications. Previous studies showed RAAS inhibitors increase the expression of ACE2, a cellular receptor for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which provokes a concern that the use of ACEI and ARB in hypertensive individuals might lead to increased mortality and severity of coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 42 publications
4
64
1
2
Order By: Relevance
“…This hypothesis was supported by initial findings that these medications were more frequently used in COVID-19 patients with cardiac injury or in those with severe form of disease ( 8 , 9 ). Nevertheless, later reports failed to show any negative relationship between adverse outcome and use of ACEI and ARB in COVID-19 patients ( 10 13 ).…”
Section: Antihypertensive Therapy In Covid-19mentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis was supported by initial findings that these medications were more frequently used in COVID-19 patients with cardiac injury or in those with severe form of disease ( 8 , 9 ). Nevertheless, later reports failed to show any negative relationship between adverse outcome and use of ACEI and ARB in COVID-19 patients ( 10 13 ).…”
Section: Antihypertensive Therapy In Covid-19mentioning
confidence: 97%
“…There was a long discussion regarding the impact of antihypertensive therapy in COVID-19 patients and particularly of angiotensin-converting enzyme inhibitors (ACEI) and blockers of angiotensin I receptors (ARB). After initial reports that showed higher prevalence of use of these medications in COVID-19 patients with cardiac injury and more severe course of disease ( 8 , 9 ), numerous original studies and meta-analysis reported no relationship with severity or mortality in COVID-19 patients ( 10 , 11 ) or even benefit of taking renin-angiotensin-aldosterone inhibitors in COVID-19 patients ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of studies of ACEI/ ARB usage among COVID-19 patients showed no significant increase in the risk of COVID-19 infection, but did show a decreased risk of severe COVID-19 and mortality in patients receiving ACEI/ARB therapy [8][9][10]. Furthermore, a meta-analysis of twenty-six studies involving 8,104 hypertensive ACEI/ARB users and 8,203 hypertensive non-ACEI/ARB users reported a significantly lower risk of mortality and a lower need for ventilator use among ACEI/ARB users [11]. We thus sought to investigate two classes of anti-hypertension medications, ACEI and ARB, for their different associations with COVID-19 occurrence and severity by using a large cohort of Veterans in the Department of Veterans Affairs (VA) COVID-19 Shared Data Resource.…”
Section: Introductionmentioning
confidence: 94%
“…Several recently published studies have confirmed that ACEIs/ARBs are not associated with increased mortality in hypertensive patients with COVID-19 and should not be discontinued [41][42][43][44]. A systematic review and meta-analysis by Wang et al (2021) supported this observation and added that the use of ACEIs/ARBs is associated with a lower risk of ventilator support [45].…”
Section: Discussionmentioning
confidence: 97%